(3JdhjM HJhVjM GddeMI GdHOQjI aj fMh Yde GdYQHjIs - (3CHhYHO Gddg TeS GdOjf eMeO Hf YHO GdOGFe Hf ehSi GdfYjej GdYSbdGfj GdHQeGhjs; (3CHh MjGf GdfMhj , eMeO Hf jhSa Hf Ydj Hf jhSa Hf MjGf GdfaRj GdZQfGWj, GKjQ GdOjf,J (B745 (3g` s ((3CMeO Hf Ydj GdQTjOj GdMfHdj s)
(3ChdgG (B:s
(3hHYO, agPG JdhjM HJhVjM GddeMI ddEeGe CHj MjGf SCdfjgG HYV ENhGfj GdeHJOFjf aj Yde GdYQHjI s
(3BNQgG (B:s
(3JHbi GdjGA SGcfI fMh gPG GdbGVj, hQCjJ GdbGVj heQQJ HGdbGVj hGddg CYde HGdUhGH s
(3HgG fXGe GdJYbjHIs
(3hcJH GdeJf GdeTQhM HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs